2021
DOI: 10.3390/molecules26103029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zinc Oxide Nanoparticles Using Rubus fairholmianus Root Extract and Their Activity against Pathogenic Bacteria

Abstract: Recently, the biosynthesis of zinc oxide nanoparticles (ZnO NPs) from crude extracts and phytochemicals has attracted much attention. Green synthesis of NPs is cost-effective, eco-friendly, and is a promising alternative for chemical synthesis. This study involves ZnO NPs synthesis using Rubus fairholmianus root extract (RE) as an efficient reducing agent. The UV spectrum of RE-ZnO NPs exhibited a peak at 357 nm due to intrinsic bandgap absorption and an XRD pattern that matches the ZnO crystal structure (JCPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…It is well-known that bulk ZnO has a band gap of 3.37 eV [21], and the decrease in the band gap energy found here can be related to the presence of defect states caused by the botanical extracts, as well as by their influence on size control during nanoparticle formation [5]. Several studies have shown the potential use of different phytochemicals (e.g., flavonoids, tannins and polyphenolics, terpenoids, amines and ketones) obtained in botanical extracts to control the size and shape of different types of nanoparticles [22,23]. From the absorbance data, the energy band gap (Eg) was estimated using Tauc's plot method (Figure 1b); the calculated Eg values are 2.99, 3.01, 3.01, 3.06, and 3.18 eV for ZnO NPs with no extract, Tagetes erecta, Lentinula edodes, Azadirachta indica, and Chrysanthemum morifolium, respectively.…”
Section: Uv-visible Spectroscopymentioning
confidence: 59%
See 1 more Smart Citation
“…It is well-known that bulk ZnO has a band gap of 3.37 eV [21], and the decrease in the band gap energy found here can be related to the presence of defect states caused by the botanical extracts, as well as by their influence on size control during nanoparticle formation [5]. Several studies have shown the potential use of different phytochemicals (e.g., flavonoids, tannins and polyphenolics, terpenoids, amines and ketones) obtained in botanical extracts to control the size and shape of different types of nanoparticles [22,23]. From the absorbance data, the energy band gap (Eg) was estimated using Tauc's plot method (Figure 1b); the calculated Eg values are 2.99, 3.01, 3.01, 3.06, and 3.18 eV for ZnO NPs with no extract, Tagetes erecta, Lentinula edodes, Azadirachta indica, and Chrysanthemum morifolium, respectively.…”
Section: Uv-visible Spectroscopymentioning
confidence: 59%
“…It is well-known that bulk ZnO has a band gap of 3.37 eV [ 21 ], and the decrease in the band gap energy found here can be related to the presence of defect states caused by the botanical extracts, as well as by their influence on size control during nanoparticle formation [ 5 ]. Several studies have shown the potential use of different phytochemicals (e.g., flavonoids, tannins and polyphenolics, terpenoids, amines and ketones) obtained in botanical extracts to control the size and shape of different types of nanoparticles [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it was determined that the inhibitory effectiveness of ZnO-NPs is highly dependent on the concentration and size used [ 57 ]. This may be attributed to the fact that nanoparticles’ reduced size makes it easier for them to pass through the microbial cell membrane, inhibiting cell growth and promoting bacterial cell death [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, different roots' extracts have been used for the synthesis of ZnO nanoparticles, as shown in Table 2. In 2021, the synthesis of spherical ZnO nanoparticles with an average size of 11.34 nm using Rubus Fairholmianus root (Dimethyl sulfoxide) extract was reported and tested against S. aureus (MIC = 157.22 µg/mL) [98]. In another study, aqueous root hair extract of Phoenix dactylifera was utilized for the synthesis of ZnO nanoparticles with a size range of 30.87 to 47.89 nm.…”
Section: Synthesis Of Zno Nanoparticles Using Leaf: (2019-2021)mentioning
confidence: 99%